Integrasi Isu-Isu Sosial Kekinian dalam Pembelajaran IPS: Sebuah Analisis Relevansi - Yushar Tanjung (UIN Fatmawati Sukarno Bengkulu, 2022)
The purpose of this study is to describe social issues in Social Sciences (Ilmu Pengetahuan Sosial, IPS) learning that are still relevant and contextually discussed today. Social studies subjects can be used as subjects that are able to increase students' social sensitivity. So that not only cognitive intelligence increases but attitudes and skills also increase. So that not only cognitive intelligence increases but attitudes and skills also increase. This study uses descriptive qualitative research methods. Data was collected by means of literature study and document analysis. Data analysis adopted from the interactive model of Miles and Huberman. Social Sciences learning materials should examine social issues that are currently developing in this context, namely, issues of peace and development. The hope is that through an interdisciplinary approach, students are able to form good and responsible citizens and global citizens. Establishing peace agents should not only target adults, but since students can be educated to become agents of world peace.